Radical transparency and digital democracy : Wikileaks and beyond - Heemsbergen, Luke (Emerald Publishing Limited, 2021)
This book tells the story of radical transparency in a datafied world. It is a story that not only includes the beginnings of WikiLeaks and its endings as a weapon of the GRU, but also exposes numerous other decentralised disclosure networks designed to crack open democracy - for good or ill - that followed in its wake. This is a story that can only be understood through rethinking how technologies of government, practices of media, and assumptions of democracy interact. By combining literatures of governmentality, media studies, and democracy, this illuminating account offers novel insights and critiques of the transparency ideal through its material-political practice. Case studies uncover evolving media practices that, regardless of being scraped from public records or leaked from internal sources, still divulge secrets. The narrative also traces new corporate players such as Clearview AI, the civic-minded ICIJ, and state-based public health disclosures in times of pandemic to reveal how they all form unique proto-institutional instances of disclosure as a technology of government. The analysis of novel forms of digital radical transparency - from a trickle of paper-based leaks to the modern digital .torrent - is grounded in analogues from the analogue past, which combine to tell the whole story of how transparency functions in and helps form democracy.
Includes index.
Keywords: Communication policy.; Information policy.; Social Science -- Media Studies.; Communication studies.; elektronické knihy; electronic books